Design of an Automated Poultry Scalding and De-Feathering Machine - John, A.; Atadious, D.; Abubakar, E. E. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
The automated poultry bird de-feathering machine is a machine which aids feather removal from birds, it helps to reduce manual labour and time spent in de-feathering process. To ensure good functionality, the boiler, scalding as well as the de-feathering compartments, were fabricated using stainless steel materials. The machine has a reservoir capacity to accommodate about 210 liters of water, a boiler compartment with 85-liter capacity. The machine uses a belt and pulley mechanism on the de-feathering compartment and a chain and sprocket mechanism on the scalding compartment. An electric motor with 3.0hp rating with 500mm and 80mm pulley on driver and driven pulley respectively were used on the de-feathering compartment, on the scalding compartment, a motor of 0.5hp with 102 teeth and 17 teeth on driver and driven sprocket were used respectively. The machine has a water pump of 1 hp which helps circulate water to the boiler, reservoir and de-feathering sprinkler hose with the help of pipes. Poultry chickens (old layer – Isa brown specie) were used to test the performance of the machine. The automated de-feathering machine has a maximum throughput capacity of 37g/s, an efficiency of 95.30%, and a de-feathering time of 32 seconds per cycle for a 10 birds capacity drum, and the processing of approximately 110 birds per hour can be achieved.